Legal Regulations of Floating Nuclear Power Plants: problems and prospects - M. N. Lysenko; V. M. Bedenko; F. Dalnoki-Veress (Московский журнал международного права, 2019)
INTRODUCTION. The article is devoted to practical and legal aspects of floating nuclear power plants (FNPPs). The first ever FNPP “Academic Lomonosov” was built in 2019 in Russia. It is a unique transportable nuclear low-power unit intended for energy and heat supply of remote port cities, industrial enterprises, gas and oil platforms. “Lomonosov” and its successor generations will have a major impact on the global nuclear energy market. The question arises how FNPPs fit into the rules of International Law.MATERIALS AND METHODS. The research was based on the analyses of international conventions on nuclear safety, security and civil liability, Treaty on the Non-Proliferation of Nuclear Weapons, IAEA documents on safeguards and standards, scholarly publications. General and special methods of legal research were used.RESEARCH RESULTS. The authors determined that in the specific case of “Academic Lomonosov” which will operate on the Russian territory no collisions with the rules of International Law are expected. However, if future serial FNPPs go for export, it will be important to analyze their compatibility with international treaties.DISCUSSION AND CONCLUSIONS. This paper concludes that FNPPs are largely compatible with the existing rules of International Law. However, there are some gaps and grey areas, especially in an export scenario. To mitigate those problems, bilateral intergovernmental agreements between the supplying and the importing states shall be concluded on their obligations in all legal and institutional issues prior to FNPP’s international shipment. Safeguards arrangement with the IAEA should be envisaged as well.